Математические методы в исторических исследованиях - Белолугов В. Б. (Вестник КИГИТ, 2006)
Экземпляры: КР (20070301) / Инвентарный номер: у61731 / Цена: 40 / Сис.шифр: 68 / Авт.знак: В 63 / ГРНТИ: 78 / ББК: 68.35(0)